FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT MODAL KERJA PADA BANK UMUM DI PROVINSI RIAU PERIODE 2009-2019 - Nanda, Zuliyan Desvani; Hendro, Ekwarso; Any, Widayatsari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine how far Third Party Funds, Non-Performing Loans, and BI interest rates affecting the optimal distribution of Working Capital Loans at Public Banks in Riau Province during the period 2009 to 2019. This study uses independent variables of Third-Party Funds, bad loans risk or Non Performing Loans, and BI Interest Rate,and dependent variable is distribution of Working Capital Loansat Public Banks in Riau Province during the period 2009 to 2019. The data used in this research is quarter data from Q.1 2008-Q.42019. Data analysis techniques that used in this study is a multiple linear regression analysis or Ordinary Least Square (OLS), while hypothesis testing uses t-test to partially test the influence of variables and the F-test to test the effect of variables simultaneously with a significance level of 5%. The results of statistical tests with the - F test show that Third Party Funds, Non Performing Loans, and BI interestrates affect simultaneously or jointly on the distribution of Working Capital Loans at Public Banks in Riau Province period 2009-2019. While the results of statistical tests with the t-test show that the Third Party Funds variable have a significant positive effect on the distribution of Working Capital Loans, the Non Performing Loans variable does not affect the distribution of Working Capital Loans, and the BI interest rates variable have a significant negative effect on the distribution of Working Capital Loans.Keywords: : Distribution of Working Capital Loans, Public Banks, Third Party Funds, Non Performing Loans, and BI Interest Rates.